The Incidence and Epidemiology of Hepatocellular Carcinoma: A Global and Regional Perspective - Venook, Alan P.; Papandreou, Christos; Furuse, Junji; Ladrón de Guevara, Laura (The oncologist (Dayton, Ohio), 2010)
Hepatocellular carcinoma (HCC) is a leading cause of cancer‐related death worldwide, and the burden of this devastating cancer is expected to increase further in coming years. The collection and analysis of epidemiologic HCC data will play a critical role in guiding future disease prevention strategies and optimizing patient management. Previous epidemiologic studies have highlighted striking global variations in the incidence of HCC, which is particularly high in much of east Asia and sub‐Saharan Africa, and lower, but on the increase, in North America and most of Europe. This variation appears to be related to the complex etiology of HCC, with different risk factors, primarily infection with hepatitis B or hepatitis C virus, responsible for driving HCC incidence rates in different regions. Although previous studies have contributed considerably to the knowledge of HCC epidemiology, there are limitations associated with the currently available data, which arise from studies performed at different times in the past, using varying methodologies, and with diverse patient populations. A new and global approach to the study of HCC epidemiology is required if HCC disease prevention and treatment strategies are to be adequately directed and supported in coming years. This article reviews key aspects of hepatocellular carcinoma and epidemiology, highlights the limitations of current data, and identifies the need for new approaches in future research.